Acid Mediated Sulfonylation of para‐Quinone Methides with Tosylmethyl Isocyanides for the Synthesis of Diarylmethyl Sulfones. Issue 28 (26th July 2021) - Kumar, Pawan; Kale, Someshwar B.; Gonnade, Rajesh G.; Das, Utpal
Abstract: An efficient, hydrochloric acid promoted reaction for the synthesis of diarylmethyl sulfones has been developed via unprecedented 1, 6‐conjugate addition reaction of tosylmethyl isocyanide (TosMIC) with para ‐quinone methides.This catalyst free reaction provides various diarylmethyl sulfones in good to excellent yields in an operationally simple method under metal free conditions. Further transformations of the productsare also demonstrated. Abstract : Reaction of tosylmethyl isocyanide (TosMIC) with a wide range of para ‐quinone methides for the synthesis of diarylmethyl sulfones has been achieved in metal free conditions. Further transformations of sulfones for spiro‐cyclizations, synthesis of chromenes and thio‐arylation were also performed.